ANALISIS HIGIENE SANITASI PENGOLAHAN DAN PEMERIKSAAN BAKTERI E. coli PADA MINUMAN AIR KELAPA MUDA YANG DIJUAL DI KELURAHAN LAUCHI KECAMATAN MEDAN TUNTUNGAN MEDAN TAHUN 2013 - Kezia Purba; Devi Nuraini Santi; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2014)
Food and beverage are important things for human being as one of principles commodity for survive and food and beverage contain any compound. The exixtence of bacteria E. coli is an indication of contamination of human feces and contaminated by the dirty substance. Urban village of Lauchi, sub-district of Medan Tuntungan is one of areas that sell the coconut water with more of consumer. Coconut water is favourited by consumer that consist of water and the flesh of coconut that mixed with sugar, orange, and ice. The research was a descriptive study. The object of this research was to know the content of E. coli in 8 samples coconut water and the implementation of hygiene sanitation. This research found the content of E. coli in all samples (8.1-240 ml samples) of coconut water and hygiene sanitation of coconut processing at urban village of Lauchi sub district of Medan Tuntungan. The study found that all of hygiene sanitation of coconut water processing at urban village of Lauchi did not fulfill the health requirement for 8 people. The content E. coli on coconut water at urban village of Lauchi did not fulfill the health requirement as mentioned in Regulation of health Minister of RI No. 492/Menkes/PER/IV/2010 concerning to the drink water quality standard for 0 per 100 ml sample. It is suggested to do the extension and supervision for the application of hygiene sanitation of the coconut water and the supervision on the important of the application of hygiene sanitation of beverage especially the coconut water to fulfill the health standard. Keywords :Hygiene sanitation, Bacteria E.coli, coconut water